PENGOLAHAN LIMBAH KAYU DENGAN TEKNOLOGI MINI COLD PRESS PADA INDUSTRI MEBEL DI SUKOHARJO - Bambang Sulistyono; Iik Endang S. Wahyuningsih; Prima Adhi Kusuma (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
The craft MSME sector is one of the leading sectors for developed countries in foreign exchange earning country. Products in handicraft industrial centers always have a higher exchange rate profitable and can create added value that is greater than other sectors. Craft Center woven bamboo as an example of a leading industry in Indonesia that is able to absorb labor as well stimulating the micro economy, but cannot be separated from facing problems, including in the field of production and management. In the production sector, the problem faced is still weak application of standards technological procedures, the process of mastering technology where most producers still use equipment simple production leading to low productivity and efficiency. Apart from that, the weak business management which causes them to be unable to increase the scale of their business. From the background of the problems above, In general, this Community Technology Dissemination activity seeks to solve partner problems with introducing appropriate technology and providing business management assistance for quality and the quantity of products from the two prospective MSME partners increased. The methods given are: 1) Introduction technology for preparing material components with a spinser (a combination of spindle and serkel machines); 2) Mini introductions cold press; 3) Introduction of finishing technology; 4) Training on diversification of processed materials into products mixmedia (mixmedia furniture design / prototype.